1982
DOI: 10.1111/j.1469-8137.1982.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

PLANT‐INDUCED CHANGES IN THE RHIZOSPHERE OF RAPE (BRASSICA NAPUS VAR. EMERALD) SEEDLINGS

Abstract: SUMMARYRape plants that were grown in thin layers of ^^P-labelled Begbroke sandy loam (initial pH 6-1) attained such high root densities (> 90 cm cm^^) that after c. 14 days, all the soil volume became rhizosphere soil. At this time, the rhizosphere pH began to decrease and the quantity of plant available P in the rhizosphere soil, as measured by the L value, exceeded the isotopically exchangeable soil P (E value), determined on samples of incubated but unplanted soil. The P concentration of the rhizosphere so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
1
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(156 citation statements)
references
References 22 publications
4
149
1
2
Order By: Relevance
“…An activity peak at 28d may have been due to exudation of the enzyme by plant roots at a time when plant demand was high. In contrast, Hedley et al (1982) found increasing acid phosphatase activity through a 35 d study but used a smaller soil volume and higher planting density than in our study. Sampling Times (days after planting) The difference between non-fumigated and fumigated soils may be attributed to the difference in microbial population or activity.…”
Section: Acid Phosphatase Enzyme Activitycontrasting
confidence: 52%
“…An activity peak at 28d may have been due to exudation of the enzyme by plant roots at a time when plant demand was high. In contrast, Hedley et al (1982) found increasing acid phosphatase activity through a 35 d study but used a smaller soil volume and higher planting density than in our study. Sampling Times (days after planting) The difference between non-fumigated and fumigated soils may be attributed to the difference in microbial population or activity.…”
Section: Acid Phosphatase Enzyme Activitycontrasting
confidence: 52%
“…Phosphorus (P) limiting conditions in soils have been shown to induce the release of organic acids into the rhizosphere in domesticated B. napus (Hedley et al 1982). The resulting reduction of the soil pH in the rhizosphere solubilizes P. The efficiency of this mechanism for enhancing plant P uptake depends largely on the availability of acid desorbable P in the rhizosphere (Hedley et al 1994).…”
Section: Historymentioning
confidence: 99%
“…As mentioned earlier, Ca, Al, and Fe hydroxides and clay particles are active participants in P sorption reactions in soils; however, the Freundlich or Langmuir equations are incapable of indicating or even suggesting which process is at work. In 1982, Hedley et al (1982) developed a sequential extraction procedure as a tool to investigate changes in individual soil P pools as affected by various management strategies. The extractable fractions have been functionally defined as follows: soluble (labile) P i is extracted in the resin; P i and organic P (P o ) are extracted in 0.5 M NaHCO 3 ; P i and P o associated with Al and Fe are extracted with 0.1 M NaOH; P i occluded in the interiors of amorphous Al or Fe hydrous oxides is extracted in 0.1 M NaOH with sonication; P i associated with Ca and primary minerals and P o are extracted with 1.0 M HCl; and the most stable P o and any remaining occluded P i are estimated after H 2 SO 4 + H 2 O 2 digestion of the residue (Hedley et al, 1982;Cross and Schlesinger 1995).…”
mentioning
confidence: 99%
“…In 1982, Hedley et al (1982) developed a sequential extraction procedure as a tool to investigate changes in individual soil P pools as affected by various management strategies. The extractable fractions have been functionally defined as follows: soluble (labile) P i is extracted in the resin; P i and organic P (P o ) are extracted in 0.5 M NaHCO 3 ; P i and P o associated with Al and Fe are extracted with 0.1 M NaOH; P i occluded in the interiors of amorphous Al or Fe hydrous oxides is extracted in 0.1 M NaOH with sonication; P i associated with Ca and primary minerals and P o are extracted with 1.0 M HCl; and the most stable P o and any remaining occluded P i are estimated after H 2 SO 4 + H 2 O 2 digestion of the residue (Hedley et al, 1982;Cross and Schlesinger 1995). Soils that have been amended with ordinary fertilizers or organic nutrient sources such as animal manure usually show differing increases in the P content of the different P pools (Hedley et al, 1982;Buehler et al, 2002.…”
mentioning
confidence: 99%